Saliva as a Forensic Tool - Shailja Chatterjee (Journal of Dental Problems and Solutions - Peertechz Publications, 2018)
Forensic science is a branch that deals with a wide plethora of areas such as anthropology, migration studies and criminology. Various biological samples have been utilized to assist a scientist towards getting answers to the myriad of questions in the field. Saliva is an easily available source from victim as well as aggressors, parent-child and siblings. Various tests have been devised to aid in identifying salivary sample constituents. This paper deals with the wide utility of saliva as a forensic tool.